Hypermethylation in Calca Promoter Inhibited ASC Osteogenic Differentiation in Rats with Type 2 Diabetic Mellitus - Lei Wang; Feng Ding; Shaojie Shi; Xingxing Wang; Sijia Zhang; Yingliang Song (Stem Cells International)
The abnormal environment of type 2 diabetes mellitus (T2DM) leads to a substantial decrease in osteogenic function of stem cells. However, the gene sequence does not vary before and after disease for the patient. This phenomenon may be related to changes in osteogenesis-related gene expression caused by DNA methylation. In this study, we established T2DM models to extract adipose-derived stem cells (ASCs) for different gene identifications through DNA methylation sequencing. Specific fragments of methylation changes in the target gene (Calca) were identified by IGV analysis. CGRP was applied to compare the effects on ASCs-T2DM morphology via phalloidin staining, proliferation through CCK-8 assay, and osteogenic differentiation with osteogenic staining, qPCR, and repair of calvarial defect. Furthermore, 5-azacytidine (5-az) was used to intervene ASCs-T2DM to verify the relationship between the methylation level of the target fragment and expression of Calca. We found that the DNA methylation level of target fragment of Calca in ASCs-T2DM was higher than that in ASCs-C. CGRP intervention showed that it did not change the morphology of ASCs-T2DM but could improve proliferation within a certain range. Meanwhile, it could significantly enhance the formation of ALP and calcium nodules in ASCs-T2DM, increase the expression of osteogenesis-related genes in vitro, and promote the healing of calvarial defects of T2DM rat in a concentration-dependent manner. 5-az intervention indicated that the reduction of the methylation level in Calca target fragment of ASCs-T2DM indeed escalated the gene expression, which may be related to DNMT1. Taken together, the environment of T2DM could upregulate the methylation level in the promoter region of Calca and then decrease the Calca expression. The coding product of Calca revealed a promoting role for osteogenic differentiation of ASCs-T2DM. This result provides an implication for us to understand the mechanism of the decreased osteogenic ability of ASCs-T2DM and improve its osteogenic capacity.